2014
DOI: 10.1536/ihj.13-321
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Cardiovascular Disorders

Abstract: SummaryImmunoglobulin4 (IgG4)-related disease is a systemic inflammatory disease characterized by elevation of serum IgG4. It involves various organs such as the pancreas (autoimmune pancreatitis), lacrimal gland (Mikulicz's disease), retroperitoneum (retroperitoneal fibrosis), aorta (aortic aneurysm and aortitis), heart (constrictive pericarditis), and pseudotumors around the coronary arteries. These disorders often coexist in accordance with progression of the disease. Because IgG4-related cardiovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 113 publications
0
75
0
Order By: Relevance
“…50) The therapeutic corticosteroid dosage required to treat IgG4-related diseases differs case-by-case, and Tajima and colleagues have suggested that treatment of IgG4-related cardiovascular diseases might require higher doses of corticosteroids than other IgG4-related diseases. 51) IgG4-related diseases can involve any organs. Therefore, it is important to survey for extra-cardiovascular lesions when IgG4-related cardiovascular disease is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…50) The therapeutic corticosteroid dosage required to treat IgG4-related diseases differs case-by-case, and Tajima and colleagues have suggested that treatment of IgG4-related cardiovascular diseases might require higher doses of corticosteroids than other IgG4-related diseases. 51) IgG4-related diseases can involve any organs. Therefore, it is important to survey for extra-cardiovascular lesions when IgG4-related cardiovascular disease is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, IgG4RD is recognized as one of the causes of vasculitis, and aneurysmal formation is thought to be the principle feature of IgG4-related vascular disease (9). In our case, not only aneurysmal formation but also stenotic lesions were observed, and these were thought to be uncommon.…”
Section: Discussionmentioning
confidence: 48%
“…18 F-fluorodeoxyglucose positron emission tomography/ CT (FDG PET/CT) has successfully been used to identify coronary artery involvement of IgG4-RD and to follow up disease activity in IgG4-RD and Takayasu vasculitis. [15][16][17][18][19][20] FDG PET/CT could therefore be considered to gauge the extent of the patient's active inflammation before and after therapy. Additionally, serological IgG4, ESR, and CRP levels have been shown to respond to treatment with corticosteroids and rituximab and seem to correlate with clinical improvement.…”
Section: Patient Presentation (Continued)mentioning
confidence: 99%